IS THE REPUBLIC OF INDONESIA AS A DEMOCRATIC STATE? (CASE STUDY THE REPUBLIC OF INDONESIA REPRESENTATIVE DEMOCRACY MODEL IN PERSPECTIVE OF LAW MAKING PROCESS) - Trijono, Rachmat (PEOPLE: International Journal of Social Sciences, 2018)
This paper focuses on the phenomenon of The Republic of Indonesia’s democracy in perspective of the lawmaking process. Democracy means ‘rule by the demos’, demos standing for ‘the many’ or ‘the people.’ There are two contrasting models of democracy: direct democracy and representative democracy. According to the 1945 Constitution of the Republic of Indonesia, that amended fourth times that is of 1999, 2000, 2001 and 2002, Indonesia used a representative democracy model to make a law. The purpose of research, the theoretically is to know that the Republic of Indonesia is not full as a democratic state, but the practice is that the Republic of Indonesia is the unique democratic state. This study uses the grounded research method, which is based on fact, and inductive analysis. Findings reveal that the Council of Representatives of the Regions (DPD) has limited authority to propose and discuss the bill, and after the decision of the Constitutional Court 92/2012, DPD participated in the discussion level 2 (Second Reading), however, the DPD role does not come to participate in approving a bill. The theoretically, that the Republic of Indonesia is not full as a democratic state, but the practice is that the Republic of Indonesia as the unique democratic state. This research further suggests to amend Article 20 Paragraph (2), Article 22D Paragraph (1) and Article 22D Paragraph (2) Indonesian constitution about first reading, second reading and joint approval of law-making process so that to be more democratic.